Pengaruh Dewan Pengawas Syariah dan Intelectual Capital Terhadap Pengungkapan Corporate Social Responsibility dengan Kinerja Keuangan Sebagai Variabel Mediasi (Studi Empiris Perbankan Syariah di Indonesia) - Nurhikmah, Febty; Winarsih, Winarsih; Kusumaningtyas, Metta (MALIA: Journal of Islamic Banking and Finance, 2018)
Corporate Social Responsibility Disclosure (CSR) is the information contained in the annual report that reveals information beyond the mandatory disclosure. Measurement of CSR disclosure in the Islamic perspective using ISR index (Islamic Social Reporting) which included the accounts of reporting CSR activities according to Islamic principles. This study aims to examine the relationship of the Sharia Supervisory Board and Intellectual Capital on Corporate Social Responsibility Disclosure with financial performance as a mediating variable. The study was conducted on annual report Islamic banking in Indonesia since the year 2010-2017. The study sample of 11 Islamic banks were selected through purposive sampling technique. Data analysis techniques used in this study is SEM-PLS using software smartpls 3.0. The result showed that Sharia Supervisory Board and Intellectual Capital have related negative and not significant to Corporate Social Responsibility Disclosure. However, based on the role of financial performance variables as variables mediating the relationship between Sharia Supervisory Board with Corporate Social Responsibility Disclosure show  negative and not significantly, while the relationship between Intellectual Capital with Corporate Social Responsibility Disclosure showed positive and significant.